PENGARUH KEPUASAN DAN KEPERCAYAAN WISATAWAN TERHADAP LOYALITAS WISATAWAN DI ANTAVAYA TOUR & TRAVEL DENPASAR - Natalia Siska Katerina; I Nyoman Sudiarta; Ni Putu Eka Mahadewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
The current digital era tourist loyalty is indispensable by the company of offline travel agent because many emerging online travel agent and one way to maintain the loyalty by always pay attention to the satisfaction and trust of tourists. This research aims to determine the influence of satisfaction and confidence of tourists towards the loyalty of tourists in AntaVaya Tour & Travel Denpasar. The sampling technique used is purposive sampling. The data analysis method used is a double linear regression analysis. Research findings suggest that from Test F and test T have positive results, it can be concluded there is a significant influence between satisfaction and confidence of tourists in AntaVaya Tour & Travel. Results of the determination of determinations obtained the result that the tourists trust variables more influential by 69.9% against tourist loyalty in AntaVaya Tour & Travel, while the satisfaction variables have an influence of 50.9% against the loyalty of tourists in the AntaVaya Tour & Travel.